2010
DOI: 10.1016/j.biopsych.2010.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Right Orbitofrontal Corticolimbic and Left Corticocortical White Matter Connectivity Differentiate Bipolar and Unipolar Depression

Abstract: Objectives The absence of pathophysiologically relevant diagnostic markers of bipolar disorder (BD) leads to its frequent misdiagnosis as unipolar depression (UD). We aimed to determine whether whole brain white matter connectivity differentiated BD from UD depression. Methods We employed a three-way analysis of covariance, covarying for age, to examine whole brain fractional anisotropy (FA), and corresponding longitudinal and radial diffusivity, in currently depressed adults: 15 with BD-type I (mean age 36.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
117
3
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(133 citation statements)
references
References 40 publications
9
117
3
4
Order By: Relevance
“…For sensitivity testing, we excluded 3 articles that used TBSS analysis [20][21][22] and then reanalyzed using GingerALE software. The result was consistent with the original meta-analysis of all 11 articles.…”
Section: Resultsmentioning
confidence: 99%
“…For sensitivity testing, we excluded 3 articles that used TBSS analysis [20][21][22] and then reanalyzed using GingerALE software. The result was consistent with the original meta-analysis of all 11 articles.…”
Section: Resultsmentioning
confidence: 99%
“…The results of these studies indicate that, compared to MDD, BD is associated with greater deep white matter hyperintensities (Dupont et al, 1995;Silverstone et al, 2003), reduced fractional anisotropy of the left superior longitudinal fasciculus (Versace et al, 2010), decreased habenula volume (Savitz et al, 2011), reduced cortical thickness in caudal middle frontal cortex, inferior parietal cortex, and precuneus (Lan et al, 2014), and increased thalamic volume (Dupont et al, 1995). In addition, Redlich et al found clusters of reduced gray matter that spanned the hippocampal formation, amygdala, putamen, insula, and temporal pole in depressed BD compared to MDD individuals, and a cluster in anterior cingulate that was reduced in MDD compared to depressed BD individuals (Redlich et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…It is characterized by alternating episodes of depression and mania, but patients spend more time in the depressive phase than in the manic phase Judd et al, 2003). Thus, BD is often misdiagnosed with unipolar depression (UD) that is characterized by depressive episodes alone (Bowden, 2001;Versace et al, 2010). Frequent misdiagnoses of one of these two conditions to another will lead to inappropriate treatment, high medical costs and poor outcomes (Bowden, 2010;Hirschfeld et al, 2003).…”
Section: Introductionmentioning
confidence: 95%